Cardiovascular disease and diabetes mortality, and their relation to socio-economical, environmental, and health behavioural factors in worldwide view. Issue 4 (April 2015) - Zahra, A.; Lee, E.-W.; Sun, L.-y.; Park, J.-H.
Abstract Background Today, non-communicable diseases, mainly cardiovascular diseases and diabetes, represent a leading threat to human health and development. This study observed mortality trends in all income group countries in relation to a wide variety of related factors like economical and environmental factors, health behaviour and health risk factors. Study design Ecological study. Method Data were analysed for 72 countries using the ecological study method. Data were collected from various sources including WHO, World Bank and previous studies. Cardiovascular disease and diabetes mortality rates for males and females were used as the dependent variables. GDP, GINI, literacy rate, urbanization, health expenditure, the number of physicians and the number of beds, BMI, western diet, blood glucose, blood pressure, serum cholesterol, physical inactivity, alcohol, and smoking were used as the independent variables initially. The final model was decided on the basis of availability of complete data and result of co-linearity test. Correlation test and linear regression were employed to identify the affecting factors for the dependent variables. Result Analysis showed that cardiovascular disease and diabetes mortality was more concentrated in middle- and low-income countries and was negatively associated with GDP, GINI, and western diet. Countries with high average blood pressure had higher mortality rates showing a positive relationship. Conclusion Non-communicable disease mortality rate is strongly associated with many economical, social, environmental, and behavioural factors. More comprehensive preventive and diagnostic strategies are needed to decrease mortality especially in low- and middle-income countries.